Endothelial cells: major players in acute myeloid leukaemia. (July 2022) - Fodil, Sofiane; Arnaud, Marine; Vaganay, Camille; Puissant, Alexandre; Lengline, Etienne; Mooney, Nuala; Itzykson, Raphael; Zafrani, Lara
Abstract: The role of the vascular microenvironment is increasingly studied in acute myeloid leukaemia (AML). Complex interactions between endothelial cells (ECs) and pre-leukaemic cells may contribute to the clonal evolution of pre-leukaemic stem cells in the bone marrow niche and to the proliferation, survival and chemoresistance of leukaemic cells. Through the expression of different adhesion molecules, ECs play a key role in the development of specific acute complications of AML, including leukostasis, acute respiratory failure, acute kidney injury or neurological complications. Moreover, in newly diagnosed patients, leukaemic cells promote endothelial activation and subsequent disseminated intravascular coagulation. Mechanisms of this bi-directional dialogue between leukaemic cells and ECs will reveal possible therapeutic targets to be explored to improve the survival of AML patients.